(untitled) (Scripta : English Department Journal, 2023)
As international language, English is leant widely around the world including Indonesia. Learning language that is not originally spoken in daily activity is difficult especially if the language has different rules with their first language. For some Indonesian, arranging good sentences in English is so difficult since English has very different rules with their first language. The difference rules from their L1 dan the target language matter because learners the to get interference from their L1 when they learn new language. One of the most difficult to learn is noun-verb agreement in sentences. using nouns in sentences is quite complicated. The difficulties are also faced by Putra Bangsa Univeristy learners. This study was mixing qualitative and quantitative methods as one with 153 participants. The data was taken from observation and multiple-choice test. This study found out, there were thirteen noun-verb agreement errors made by EL from Putra Bangsa University and three reasons of noun-verb agreement errors made by EL from Putra Bangsa University.